APPLICATION OF THE SELF-REGULATED LEARNING (SRL) METHOD TO IMPROVE THE LEARNING OUTCOMES OF STUDENTS IN CLASS V SD NEGERI PEUNAGA, WEST ACEH DISTRICT - Sri Ayuni; Hadiid Thaariq, Shah Mohd (International Journal of Students Education, 2023)
The problem of this study is whether the application of self-regulation learning strategies can improve learning outcomes on the theme of maintaining the health of the human respiratory organs for fifth grade students at SD Negeri Peunaga, West Aceh district. The purpose of the research that will be carried out by researchers is to find out whether the application of the Self-Regulation Learning learning model can improve student learning outcomes. The subjects in this study were fifth grade students consisting of 17 students. The object in this study is the application of self-regulation learning strategies. This research includes Classroom Action Research (PTK) conducted in two cycles. Each cycle consists of four stages, namely design, implementation, observation, and reflection. Data collection techniques are through tests and observations made during the learning process. Data and initial tests of students’ learning completeness levels are written in the form of tables and diagrams. In the pre-cycle test the level of completeness of student learning classically obtained 3 students (17.65%) who completed and 14 students (82.3 5%) who did not complete. In cycle I it increased to 5 students (29.41%) who completed, in cycle II it increased again to 14 students (82.35%) who completed. The results of observations of class management experienced an increase from cycle I obtaining an average of 2.28 pretty good categories, cycle II obtaining an average of 2.6 good categories, and cycle III obtaining an average of 3.69 very good categories.